People skills for public managers - McCorkle, Suzanne; Witt, Stephanie L. (Routledge, 2014)
This book fills the need for a communication-based, public sector framed book. The authors combine just enough basic theory about communication with specific skill development in areas of immediate interest to those who work in the public sector. It also features a strong "practice" orientation, with plentiful boxed applications (Insights from the Field, Skill Development boxes, Case Studies). It concludes with an especially useful summary chapter that describes the ten essential skills for successful communication.